2018
DOI: 10.2460/javma.253.5.586
|View full text |Cite
|
Sign up to set email alerts
|

Results of a survey of Veterinary Orthopedic Society members on the preferred method for treating cranial cruciate ligament rupture in dogs weighing more than 15 kilograms (33 pounds)

Abstract: OBJECTIVE To determine which method (lateral fabellotibial suture [LFS], tibial plateau leveling osteotomy [TPLO], tibial tuberosity advancement [TTA], or tightrope-like braided multifilament suture secured with metallic buttons [TR]) Veterinary Orthopedic Society (VOS) members preferred for treating cranial cruciate ligament rupture (CCLR) in dogs weighing > 15 kg (33 lb), identify factors associated with this preference, and assess concerns related to surgical implant material used. DESIGN Cross-sectional st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 87 publications
0
47
0
1
Order By: Relevance
“…The TPLO is the most common orthopedic surgery for stabilization of cranial cruciate ligament deficient stifles in dogs [12,13]. Patients undergoing a TPLO and other orthopedic procedures are often subjected to activity restriction, and the development of disuse muscle atrophy following orthopedic injuries has been documented [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The TPLO is the most common orthopedic surgery for stabilization of cranial cruciate ligament deficient stifles in dogs [12,13]. Patients undergoing a TPLO and other orthopedic procedures are often subjected to activity restriction, and the development of disuse muscle atrophy following orthopedic injuries has been documented [15].…”
Section: Discussionmentioning
confidence: 99%
“…Cranial cruciate ligament (CCL) rupture is the most common stifle injury in medium and large breed dogs, ultimately resulting in pain, lameness, and secondary muscle atrophy of the affected limb [9]. While various surgical procedures are described for the repair of CCL rupture, the tibial plateau leveling osteotomy (TPLO) is the most common repair technique for the cranial cruciate ligament deficient stifle, with the ultimate goal of providing functional stifle joint stability [10][11][12][13]. There have not been any studies addressing the effect of disuse muscle atrophy on stifle joint stability or on interventions to mitigate disuse muscle atrophy in dogs with CCL rupture.…”
Section: Introductionmentioning
confidence: 99%
“…The abrasive characteristics of this suture to soft tissues (cheese‐wiring effect) and suture breakage of biodegradable and metal bone anchors have been reported . In addition, von Pfeil et al surveyed veterinary orthopedic surgeons who reported only a 1.6% preference for using the same suture materials in dogs with CCL deficient stifles weighing >15 kg primarily because of major complications, among which infection rather than cheese‐wiring or implant failure was most common. Although this is a cause for concern, the impact of the abrasive nature of the suture has not been documented in toy breed dogs.…”
Section: Discussionmentioning
confidence: 99%
“…The TPLO is currently the most commonly recommended procedure by veterinary surgeons for the treatment of CCL rupture. 10,27 That said, several other procedures exist and may be alternatively selected for the treatment of CCL rupture. The TPLO is a dynamic osteotomy-based procedure that neutralizes tibiofemoral shear force during weight bearing.…”
Section: Clinical Outcome With Tplomentioning
confidence: 99%
“…A variety of static and dynamic stifle joint procedures have been previously described, with the tibial plateau leveling osteotomy (TPLO) emerging as the preferred treatment option for present-day surgeons. 10 This is due to the TPLO demonstrating exceptional and repeatable clinical outcomes when compared to other surgical options.…”
Section: Introductionmentioning
confidence: 99%